STUDY REGARDING THE BEHAVIOUR OF MATERIALS USED FOR THE ROOT RESTORATIONS IN ART TECHNIQUE - Galina Pancu; Sorin Andrian; Gianina Iovan; Angela Ghiorghe; Irina Nica; Claudiu Topoliceanu; Antonia Moldovanu; Simona Stoleriu (Romanian Dental Association for Education, 2016)
Root dental caries represent an issue focusing many dental researchers. However due to morphologic and structural particularities of cement and root dentine as well as the nearby of dental pulp, root dental caries is a challenge regarding therapeutical success. The aim of this study was to assess the clinical performance of two restorative materials: glassionomer cement CGI with high density and a resin-modified glassionomer cement (RMGC), using ART technique in complex cervical root cavities. The assessment of restorations quality parameters was performed after 1 and 6 months using ART assessment criteria. After 6 months, success rate was 100 % for GC Fuji II LC and 96,6 % for Fuji VIII. After 6 months, success rate of ART technique for all 20 patients was 98,3 %. A higher success rate of our study, comparing with literature data, is due to the improvement of ART technique combined with the use of superior dental materials. (GC Fuji VIII, GC Fuji II LC), as well as the use of photopolimerisable resin-modified glassionomer cement GC Fuji II LC. More the use of conditioner, previously to the insertion of restoration material, improves significantly the adhesion and prevent microleakage. The superior esthetics and surface parameters are due to the use of varnish. Our study proved that ART method for aged patients, in cervical root dental caries treatment, was more efficient, both for simple cavities (1 surface) and complex cavities, after a 6 months periode. The results were promising for both researched glassionomer cements.